1988
DOI: 10.1063/1.340390
|View full text |Cite
|
Sign up to set email alerts
|

Wall-induced inhomogeneities in the low-pressure Hg-Ar positive column

Abstract: Radial variations of the Hg(63P0,1,2) densities are measured in a low-pressure Hg-Ar discharge and the results are compared with a model. The 34-mm-diam discharge tube is operated in the vicinity of 400-mA current, 6.4-mTorr Hg pressure, and 2.81-Torr Ar pressure. A tunable dye laser beam passes axially through the discharge tube, and densities are measured using both a saturated absorption technique and an interference technique. The model incorporates continuity equations for Hg excited and ionic states, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Rate coefficients for electron impact processes are determined using Boltzmann's equation. It is here that the present computational model differs most significantly from that reported previously [5][6][7], where some functional form was assumed for the electron energy distribution (EED). Here the EED is computed using a method essentially equivalent to that described in [20].…”
Section: Kinetic Model Of Electron Distribution Functionmentioning
confidence: 85%
See 2 more Smart Citations
“…Rate coefficients for electron impact processes are determined using Boltzmann's equation. It is here that the present computational model differs most significantly from that reported previously [5][6][7], where some functional form was assumed for the electron energy distribution (EED). Here the EED is computed using a method essentially equivalent to that described in [20].…”
Section: Kinetic Model Of Electron Distribution Functionmentioning
confidence: 85%
“…The model is derived in part from previous models constructed to describe lowpressure rare gas/mercury positive column discharges [5][6][7]. (All references to 'mercury-based' discharges and lamps in this paper refer to low-pressure discharges where the mercury vapour pressure is 3-30 mTorr, corresponding to a density range 10 14 -10 15 cm −3 .…”
Section: Discharge Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Radially resolved experimental results show rather flat profiles of the Hg triplet states densities over the column radius, which are different than the general assumption of a Bessel profile. 70,87,88,91 A complete model would self-consistently couple the electron kinetics, the excited state population kinetics, and the radiative transfer equation including nonlocal photopumping.…”
Section: Discussionmentioning
confidence: 99%
“…The models calculate time-dependent RT using the propagator function method developed by Lawler et al, 9 and include atomic collisions between neutral species as well as electron-neutral impact collisions. In the earlier models dealing with resonance radiation transport, [10][11][12] fluid models were adopted and the redistribution of radiative state density was not evaluated with full calculation of the Holstein equation 13 but with the effective trapping factor. However, it was reported that the effective trapping factor approximation does not give accurate results when the lowest eigenmode of Holstein's solution is not the dominant one.…”
Section: Introductionmentioning
confidence: 99%